Peran Elemen Visual Sebagai Strategi Komunikasi Pemasaran Pada Kemasan Produk - Susilawati; Nabila Fajrina; Rachmadita Dwi Pramesti (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2023)
The increasingly fierce market competition demands manufacturers to act as communicators, employing various communication strategies to ensure their products are always remembered and chosen by consumers. Beyond showcasing product advantages, there is a need for a strong visual identity. This research aims to illustrate how manufacturers implement marketing communication strategies through packaging design. Packaging no longer serves solely as a container and protector; it also functions as a visual communicator to consumers. Thus, packaging requires attractive design elements, including brand, logo, color, illustration, typography, layout, and shape. Perception, the process of receiving and interpreting sensory stimuli, plays a crucial role in the attractiveness of packaging design, as the brain and eyes seek simplicity and balance in everything they perceive. This research employs a qualitative descriptive method focusing on marketing communication strategies and packaging design. The purposive sampling technique and an interactive data analysis model were utilized to obtain direct data from observations. The results depict that the visual elements in packaging design serve as effective tools for communicating product information, fostering interaction with consumers, and creating a brand experience that can attract consumers to become customers.